Aplikasi Filling Rekam Medis Menggunakan Metode Algoritma Turbo Boyer Moore - Beni Harzani; Diana Diana (Universitas Negeri Medan, 2020)
Nagaswidak Health Center is one of the community health centers that is quite large and has complete facilities. But the problem that is often faced by officers in the puskesmas is the medical record data processing system which is still manual, causing the accumulation of patient medical record file data, in addition to patients who have been checked before and lost their medical records, it is very difficult for officers to find back, so the officer made a new medical record data. To overcome this problem, a Medical Records Filling Application was made at the Nagaswidak Health Center which includes the processing of medical records, patient data, drug data, action data, doctor data, and admin logins. So that the data search problem is not difficult, the turbo boyer moore algorithm method is applied which is expected to later be able to facilitate the search for patient data in the medical record filling application. Based on the test results Boyer Moore's Algorithm successfully applied to search for the beginning of a word, middle word, and final word. And the level of ease and usefulness of medical records application using Boyer Moore's algorithm obtained results that the level of ease is 80% and 100% usability rate.